Patient and Kidney Allograft Survival in Recipients With End-Stage Renal Disease From Amyloidosis. Issue 2 (February 2018) - Sawinski, Deirdre; Lim, Mary Ann; Cohen, Jordana B.; Locke, Jayme E.; Weiss, Brendan; Hogan, Jonathan J.; Dember, Laura M.
Abstract : Background: Outcomes after kidney transplantation for patients with amyloidosis-associated end-stage renal disease (ESRD) have not been well characterized. Methods: We performed a retrospective propensity score matched cohort study with Cox proportional hazards modeling using data from the United Network of Organ Sharing including patients transplanted from 1987 to 2015 (N = 310 629). Results: Amyloidosis patients (N = 576) had higher rates of death (hazard ratio [HR], 1.58; 95% confidence interval [CI], 1.28-1.95) and graft loss (HR, 1.49; 95% CI, 1.19-1.87) compared with nonamyloidosis patients. The results were similar when the cohort was restricted to patients transplanted on or after 2001 (HR, 1.72; 95% CI, 1.31-2.26 for death; HR, 1.77; 95% CI, 1.35-2.33 for graft loss). However, there was no significant difference in risk of death or graft loss when amyloidosis patients were compared with those with diabetes-associated ESRD (mortality: HR, 0.99; 95% CI, 0.84-1.17; allograft loss: HR, 1.00; 95% CI, 0.84-1.20), or when compared with elderly patients (age, >65 years at the time of transplant) (mortality: HR, 0.99; 95% CI, 0.81-1.21; graft loss: HR, 1.02; 95% CI, 0.82-1.26). Conclusions: For patients with amyloidosis-associated ESRD deemed suitable for transplantation, patient and graft survivals are diminished compared to kidney transplant recipients overall, but are comparable to other high-risk subgroups. Abstract : This retrospective analysis of UNOS data of patients transplanted from 1987-2015 (28 years) with a diagnosis of amyloidosis shows that although the risk of death or graft loss is higher than the general transplant population it is similar to that of diabetics. Supplemental digital content is available in the text.